MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SEJARAH MATERI PERADABAN AWAL MASYARAKAT DI DUNIA YANG BERPENGARUH TERHADAP PERADABAN DI INDONESIA MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA KELAS X 3 SMA NEGERI 4 BARABAI TAHUN PELAJARAN 2013/2014 - Riswiyani Riswiyani (Universitas Lambung Mangkurat, 2014)
The aims of this research is to find out activities and learning outcomes of History major grade 3 of SMAN 4 Barabai. This research was classroom action research ( PTK )that used qualitative approach. The techniques for collecting data were observation to the students learning activities and teacher activities in teaching and learning. Meanwhile, the learning outcomes taken from the pretest and postest scores, and also questionnaires which are given to students after the lessons in order to get their responses. As the result, showed that the students’ learning activities have been increasing in the first cycle with 84% and in the second cycle with 92%. The learning outcomes have been increasing in the first cycle with 83.3% and in the second cycle with 95.8%. The individual learning completeness has been increasing which is seen from the average learning outcomes, and positive responses are shown by the students during the lessons using make-a-match learning model.Key Word: Activity, Learning Outcome of History, Make-a-match model.